A discussion about the Socioeconomic Observatory of Covid-19 through a state, regional and national perspective (Research, Society and Development, 2020)
The new coronavirus (Covid-19) is considered a virus of rapid transmission and dissemination, thus brings concern at the international level, and its impacts go beyond health issues.There is a great risk of the pandemic generated by this vírus, mainly in the Latin American context, due to the high economic and social inequalities. In this sense, we highlight the importance of an observatory with socioeconomic data on covid-19 impacts and the simulation of the impacts of economic measures scenarios, whose issue is portrayed as the objective of this study, seeking to observe the aspects of Rio Grande do Sul (RS), brazilian macro-regions and the Brazilian economy as a whole. In this context, an indirect technique of data processing is used from a bibliographic survey, being an exploratory study. As expected results, the relevant theoretical and technical contribution to the theme of socioeconomic issues related to Covid-19, supported by empirical evidence, contributed to build a better society based on education and science, having as limitations the projections and predictions made only in the socioeconomic scope.